(untitled) (Indian Internet Journal of Forensic Medicine and Toxicology, 2004)
Alcoholism is a common medico-legal problem. Studies have shown the incidence of vehicular accidents is more among the drunk drivers. The association of alcohol is also seen in homicides, suicides and assault cases. Recently in capital city of Delhi courts have directed the hospitals to use breath analyzer in cases under motor vehicular act to detect blood alcohol. Therefore a pilot study was conducted to compare the reading of breath analyzer of different makes in the same individual at same time. These readings were also compared with the Gas Liquid Chromatography (GLC) technique. Alcoholmeter of five different makes showed lot of variation then the GLC results which were also variable but at lower side. However authors are not questioning the validity and correctness of the Breath analyzers, which are used world over, they simply want to stress the need for proper use, calibration and further studies in Indian context on this subject to avoid any legal complications